A CONFLICT OF COLONIAL CULTURES IN THE EDUCATIONAL SUB-SYSTEMS IN AFRICA: CELEBRATING FIFTY YEARS OF POLITICAL AND NOT EDUCATIONAL SOVEREIGNTY IN CAMEROON - Ngalim, Valentine Banfegha (European Scientific Journal, ESJ, 2014)
This paper sets out to study the conflict of colonial cultures in the educational system in Cameroon. The problem identified in this conflict is the absence of an common vision in the provision of educational values for citizens in the same country. Lack of a common vision provokes problems of equity and quality education. The argument advanced here is that colonial cultures are principal determinants of the educational values in Cameroon. This position is expressed as educational alienation. Harmonization of the educational sub-systems is proposed as a possible means through promoting a culture that is typically Cameroon within the framework of her diversity of cultures. To attain this objective, this paper employs a mixed method of research. The quantitative and qualitative methods are used to prove the hypothesis that some problems of education in Cameroon could be traced in the conflict of colonial cultures. This problem is explained in Dewey’s democratic conception of education as educational alienation. The multicultural theory of education rejects the prominence of colonial cultures to the relative neglect of indigenous cultures in Cameroonian school system (Bank1994). With this theory, educational sovereignty is still to be realized in Cameroon. Therefore, after fifty years of political independence, one is still to think of education sovereignty in Cameroon. Harmonization of the educational sub-systems offords a possible perspective. This objective has to be taken with a multicultural rather than a bicultural overtone. This is to maintain the Cameroon reality of unity in diversity. This vision strengthens the politics of unity and national integration.